2021
DOI: 10.3390/molecules26071836
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids Used as Medicines: Structural Phytochemistry Meets Biodiversity—An Update and Forward Look

Abstract: Selecting candidates for drug developments using computational design and empirical rules has resulted in a broad discussion about their success. In a previous study, we had shown that a species’ abundance [as expressed by the GBIF (Global Biodiversity Information Facility)] dataset is a core determinant for the development of a natural product into a medicine. Our overarching aim is to understand the unique requirements for natural product-based drug development. Web of Science was queried for research on alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 62 publications
(71 reference statements)
1
64
0
1
Order By: Relevance
“…These findings partly explain the negative chronotropic and ionotropic effects of F. indica. Previous studies have shown that alkaloids, flavonoids, and phenols exhibit cardioprotective activity [60]. Therefore, the content of alkaloids, flavonoids, and phenols reported in F. indica extract might be responsible for myocardial cell membrane protective activity.…”
Section: Discussionmentioning
confidence: 93%
“…These findings partly explain the negative chronotropic and ionotropic effects of F. indica. Previous studies have shown that alkaloids, flavonoids, and phenols exhibit cardioprotective activity [60]. Therefore, the content of alkaloids, flavonoids, and phenols reported in F. indica extract might be responsible for myocardial cell membrane protective activity.…”
Section: Discussionmentioning
confidence: 93%
“…Alkaloids can be subdivided into numerous sub-classes. As stated by Heinrich et al in October 2020, the Dictionary of Natural Products included 27,683 alkaloids [ 20 ]. Organosulfur compounds include isothiocyanates, indoles, allylic sulfur compounds, and sulforaphane [ 15 ] …”
Section: Phytochemicals Are Instrumental To Advance Cancer Managementmentioning
confidence: 99%
“…Alkaloids are one of the largest family of natural products with a diverse range of medical applications, including analgesic, central nervous stimulant/depressant, anticholinergic, antitumour, and antiparasitic activities [ 9 , 10 , 11 , 12 ]. They have been used in traditional medicine for centuries because of their presence in bacteria, fungi, plants, amphibians, insects, mammals, and humans; more than 18,000 alkaloids have been discovered thus far [ 13 ].…”
Section: Overview Of Alkaloids In the 21st Centurymentioning
confidence: 99%